Remote sensing as a monitoring tool for cropping area determination in smallholder agriculture in Tanzania and Uganda - Quiróz, R. (International Potato Center, 2015)
This document highlights the efforts that are being led by the International Potato Center (CIP) to develop cost-effective methods that utilize UAV as a platform to collect accurate and timely data for agricultural statistics. Beyond the platforms, low-cost and high quality sensors for specific agricultural applications, as well as the software required to process and analyze the acquired data are being developed.